Comparison of jers-1 and radarsat synthetic aperture Radar data for mapping mangrove and its biomass - Hashim, Mazlan; Wan Kadir, Wan Hazli (1999)
This paper has reviewed comparison of classification of mangrove forest at species-level, and estimation of mangrove biomass using JERS-1 SAR and Radarsat SAR (standard mode) data. Both of these comparisons were made at selected test site in Sungai Pulai Mangrove Forest Reserve in Malaysia. The results demonstrated the utility of SAR data as potential source in mapping mangrove classes and indicator for biomass. Although there has been limited availability of exhaustive sampling points done accessibility at the test site, but the results indicated the evidence of C and L band utility for mangrove mapping and biomass estimation.